Noninvasive assessment of hepatic steatosis grades by ultrasound derived fat fraction in metabolic dysfunction associated steatotic liver disease - Meng Sun; Mingwei Zhong; Fangqiong Luo; Meng Lan; Xinru Zhang; Wei Nie; Zhe Ma (Scientific Reports)
Abstract To evaluate the diagnostic performance of ultrasound-derived fat fraction (UDFF) and clinical prediction models in assessing hepatic steatosis grades in MASLD patients, with liver biopsy as reference standard.A total of 85 obese patients who were found to have fatty liver by B-mode ultrasound and underwent UDFF measurement, with liver biopsy available, were enrolled. The diagnostic performance of UDFF, clinical prediction models including fatty liver index (FLI), hepatic steatosis index (HSI), ZheJiang University index (ZJU index) and lipid accumulation product (LAP) for hepatic steatosis was assessed. The areas under receiver operating characteristics curves (AUROCs) were utilized to determine the diagnostic efficacy. DeLong test was used to compare the diagnostic performance of different noninvasive methods for hepatic steatosis. The UDFF values of S1, S2 and S3 groups were 17.53 ± 7.49%, 25.00 ± 5.41% and 27.58 ± 6.55%, respectively (P < 0.001). UDFF values were significantly positively correlated with histologic steatosis grades (r = 0.531, P < 0.001). In the ≥ S2 group, the AUROC of UDFF was higher than that of FLI and LAP (P < 0.05), but not significantly different from that of HSI and ZJU index (P > 0.05). In the ≥ S3 group, the AUROC of UDFF was higher than that of FLI, ZJU index and LAP (P < 0.05), but not significantly different from that of HSI (P > 0.05). The UDFF proves effective in assessing hepatic steatosis in patients with MASLD, and its diagnostic efficacy exceeded that of FLI and LAP, but there was no significant difference with HSI, ZJU index in the ≥ S2 group, and with HSI in the ≥ S3 group.